2018
DOI: 10.17743/jaes.2018.0011
|View full text |Cite
|
Sign up to set email alerts
|

Determination and Validation of Mix Parameters for Modifying Envelopment in Object-Based Audio

Abstract: Envelopment is an important attribute of listener preference for spatial audio reproduction. Object-based audio offers the possibility of altering the rendering of an audio scene in order to modify or maintain perceptual attributes-including envelopment-if the relationships between attributes and mix parameters are known. In a method of adjustment experiment, mixing engineers were asked to produce mixes of four program items at low, medium, and high levels of envelopment in 2-channel, 5-channel, and 22-channel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 15 publications
1
9
0
Order By: Relevance
“…This is supported by other studies that have found that spatial attributes contribute to overall listener preference [26,27,52]. This suggests that OBA systems could deliver improvements to listener experience if they employed optimized rendering rules for spatial attributes such as envelopment; recent research has shown that it is possible to adapt object-based mixes to result in different levels of envelopment [53]. Relationships with large and medium effect sizes can be observed between envelopment and all of the processes apart from spread.…”
Section: Discussionsupporting
confidence: 71%
“…This is supported by other studies that have found that spatial attributes contribute to overall listener preference [26,27,52]. This suggests that OBA systems could deliver improvements to listener experience if they employed optimized rendering rules for spatial attributes such as envelopment; recent research has shown that it is possible to adapt object-based mixes to result in different levels of envelopment [53]. Relationships with large and medium effect sizes can be observed between envelopment and all of the processes apart from spread.…”
Section: Discussionsupporting
confidence: 71%
“…The question arises if integrating more loudspeakers will also enhance the overall listening experience for listeners. In a study comparing stereo, surround, Ambisonics, 9-channel, and 22-channel stereophony Francombe et al [4] showed that listeners preferred systems with more than five channels for different types of broadcast content.…”
Section: Introductionmentioning
confidence: 99%
“…A preference study conducted by Francombe et al [25] suggested that envelopment was the most important perceptual factor when comparing different spatial audio reproduction methods. Similarly, Rumsey et al [26] found that envelopment was more desirable than frontal spatial fidelity.…”
Section: Evaluation Of Spatial Audio Reproductionmentioning
confidence: 99%
“…In particular, the immersive/enveloping 5 code received 14 positive comments (and no negatives)-twice as many as any other code-and was mentioned alongside the spread of sounds (which had the third highest frequency of positive comments, N = 5) as well as effect on drama, effect on story, and engagement. In a study into the relationship between listener preference and perceptual attributes for a wide range of spatial audio systems (mono to 22-channel), Francombe et al [25] found that the attribute "envelopment" has the largest influence on listener preference. This suggests that MDO could provide significant improvements to the listener experience (compared to stereo) by increasing immersion or envelopment.…”
Section: Perceptualmentioning
confidence: 99%